The Role of Organizational Commitment in Mediating Job Satisfaction, Organizational Culture, and Motivation on Authorized Partner Performance - Iskandar, Yenny; Amir, Amri; Johannes, Johannes; Suharmiyati, Suharmiyati (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2024)
Establishing authorized partners for telecommunication providers puts human resource management at odds, as their inherent externalities require further effort to manage. This study delves into this complex management by focusing on the mediating role of organizational commitment in job performance, with organizational culture and motivation as the predictors. The sample (N: 157) is drawn from the authorized partners of the largest telecommunication company in Indonesia, for the analysis employing the partial-least-square structural-equation modeling (PLS-SEM). The findings show a moderate acceptance of the proposed research model, as indicated by the R2 revelation. The study reveals that organizational commitment can mediate the effects of organizational culture and motivation on the performance of authorized partners. This underscores the importance of organizations having sufficient control over their external distributors by enhancing the positive culture experience and motivational factors in extensive training and engagement settings, thereby providing valuable insights for human resource management.